Altering Early Life Gut Microbiota Has Long-Term Effect on Immune System and Hypertension in Spontaneously Hypertensive Rats - Abboud, Francois M.; Cicha, Michael Z.; Ericsson, Aaron; Chapleau, Mark W.; Singh, Madhu V. (Frontiers in Physiology, 2021)
Hypertension is regulated by immunological components. Spontaneously hypertensive rats (SHR) display a large population of proinflammatory CD161+ immune cells. We investigated the effect of early postnatal gut microbiota on the development of the immune system and resulting hypertension in the SHR. We first examined the microbial populations in the fecal samples of SHR and normotensive control WKY using 16s rDNA sequencing. We found that in the newborn SHR (1-week old) the gut microbiota was qualitatively and quantitatively different from the newborns of normotensive WKY. The representation of the predominant bacterial phylum Proteobacteria was significantly less in 1-week old SHR pups than in WKY (94.5% Proteobacteria in WKY vs. 65.2% in SHR neonates). Even within the phylum Proteobacteria, the colonizing genera in WKY and SHR differed dramatically. Whereas WKY microbiota was predominantly comprised of Escherichia-Shigella, SHR microbiota was represented by other taxa of Enterobacteriaceae and Pasteurellaceae. In contrast, the representation of phylum Firmicutes in the neonatal SHR gut was greater than WKY. Cross-fostering newborn SHR pups by lactating WKY dams caused a dramatic shift in 1-week old cross-fostered SHR gut microbiota. The two major bacterial taxa of phylum Proteobacteria, Enterobacteriaceae and Pasteurellaceae as well as Lactobacillus intestinalis, Proteus, Romboustia and Rothia were depleted after cross-fostering and were replaced by the predominant genera of WKY (Escherichia-Shigella). A proinflammatory IL-17F producing CD161+ immune cell population in the spleen and aorta of cross-fostered SHR was also reduced (30.7% in self-fostered SHR vs. 12.6% in cross-fostered SHR at 30 weeks of age) as was the systolic blood pressure in adult cross-fostered SHR at 10 weeks of age. Thus, altered composition of gut microbiota of SHR toward WKY at early neonatal age had a long-lasting effect on immune system by reducing proinflammatory immune cells and lowering systolic blood pressure.